Cardiogenic Shock Among Patients with and without Acute Myocardial Infarction in a Latin American Country: A Single-Institution Study - Héctor González-Pacheco; Daniel Manzur-Sandoval; Rodrigo Gopar-Nieto; Amada Álvarez-Sangabriel; Carlos Martínez-Sánchez; Guering Eid-Lidt; Alfredo Altamirano-Castillo; Salvador Mendoza-García; José Luis Briseño-Cruz; Francisco Azar-Manzur; Diego Araiza-Garaygordobil; Daniel Sierra-Lara; et al. (Ubiquity Press, 2021)
Background: Latin America has limited information about the full spectrum cardiogenic shock (CS) and its hospital outcome. This study sought to examine the temporal trends, clinical features and outcomes of patients with CS in a coronary care unit of single Mexican institution. Methods: This was a retrospective study of consecutive patients hospitalized with CS in a Mexican teaching hospital between 2006-2019. Patients were classified according to the presence or absence of acute myocardial infarction (AMI). Results: Of 22,747 admissions, 833 (3.7%) exhibited CS. Among patients with AMI (n = 12,438), 5% had AMI-CS, and in patients without AMI (n = 10,309), 2.3% developed CS (non-AMI-CS). Their median age was 63 years and 70.5% were men. Cardiovascular risk factors were more frequent among the AMI-CS group, whereas a history of heart failure was greater in non-AMI-CS patients (70.1%). In AMI-CS patients, the median delay time was 17.2 hours from the onset of AMI symptoms to hospital admission. Overall, the median left ventricular ejection fraction (LVEF) was 30%. Patients with CS at admission showed end-organ dysfunction, evidenced by lactic acidosis, renal impairment, and elevated liver transaminases. Of the 620 AMI-CS patients, the main cause was left ventricular dysfunction in 71.3%, mechanical complications in 15.2% and right ventricular infarction in 13.5%. Among the 213 non-AMI-CS patients, valvular heart disease (49.3%) and cardiomyopathies (42.3%) were the most frequent etiologies. In-hospital all-cause mortality rates were 69.7% and 72.3% in the AMI-CS and non-AMI-CS groups, respectively. Among AMI-CS patients, renal dysfunction, diabetes, older age, depressed LVEF, absence of revascularization and the use of mechanical ventilation were independent predictors of in-hospital mortality. However, in the non-AMI-CS group, only low LVEF and high lactate levels proved significant. Conclusions: This study demonstrates differences in the epidemiology of CS compared to high-income countries; the high mortality reflects critically ill patients and the lack of contemporary effective therapies in the population studied.